Research into operational parameters of diesel engines running on RME biodiesel - Lebedevas, Sergejus; Vaicekauskas, Andrius; Lebedeva, Galina; Janulis, Prutenis; Makarevičienė, Violeta (Transport, 2006)
The results of motor experimental researches on operational parameters of diesel engines F2L511 and A41 are presented in the publication. Change of harmful emission of exhaust gases was determined and evaluated, fuel economy and thrust characteristics of diesel engines running on RME biodiesel compared to diesel fuel. The influence of technical condition of fuel injection aggregates was evaluated for parameters of harmful emission of diesel engines running on biodiesel by simulation of setback of fuel injection in alowable range of technical conditions ‐ the coking of nozzles of fuel injector. The complex improvement of all ecological parameters was evaluated by optimisation of fuel injection phase of diesel engines running on RME biodiesel. Objectives and aspects of further researches on indicator process of diesel engines were determined. First Published Online: 27 Oct 2010